Dynamics of social participation in the Municipal Environmental Council of the Açu-Mossoró Territory (RN): Reality from a documentary perspective (Research, Society and Development, 2021)
The study aimed to identify the dynamics of participation from a formal point of view, investigating the functioning of the decision-making process by the performance of the counselors evidenced in the minutes and resolutions. The approach of this research was constituted by the qualitative method, descriptive research and documentary research because it uses documents from the Municipal Council for the Defense of the Environment (CONDEMA), such as minutes, reports and resolutions, whose textual analysis was made by the interpretative analysis. The documentary research, obtained in the SISMUMA Project, in CONDEMA and in the Official Journal of Mossoró, aimed to analyze the performance of CONDEMA from a legal and formal point of view, as a way of characterizing the institutional arrangement, the functioning and the activities of the Council . Finally, what was observed in the formal dimension, detailed by the view of the board members, is that the Board presented some problems, related to the asymmetry of information and participation and the large number of agendas with technical matters of management, which need to be reflected and strengthened. in the participatory decision-making process, as it has impaired the performance of the members of the councilors in a way that provides an ideal participation since there is a tendency to legitimize participation in the actions of the municipal public power.